The wisdom of the book «Alone with myself. Reflections» by Marcus Aurelius - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
This article examines the views of the ancient Roman philosopher Marcus Aurelius on the structure of the universe and the norms of Stoic morality, as set forth in his book «Alone with myself. Meditations». The concepts of the human soul and mind (spirit and intellect) are explored. It demonstrates how the philosopher distinguishes between those aspects of human behaviour predetermined by divine providence and those aspects that depend on the individual and are closely linked to their attitude toward themselves. In this regard, the ancient Roman Stoic’s book focuses particularly on a person’s life position, their value orientations, their ideas of good and evil, their self-esteem, and their attitudes toward others. The article analyses the opinions expressed in the work on the meaning of life, the goals and tactics of human activity, positive personal and professional qualities, and education and self-improvement.
Keywords: philosophy; morality; stoicism; man; mind; soul; good; evil